Remote rearrangement of the metal center in a (η6-C6Me6)Ru(ii) complex1. Issue 24 (25th March 2015) - Takano, Koichi; Ikeda, Yousuke; Kodama, Shintaro; Ishii, Youichi
<x xml:space="preserve">Abstract</x> Reaction of [(η6-C6Me6)Ru(Ph)(PMe3)]+ with internal alkynes gave rise to the 1, 4-Ru migration to form the o-vinylaryl complex, providing the first example of 1, 4-metal migration of a group 8 metal center; in one case further isomerization to an η3-allyl complex was observed.